Sociodemographic and visual characteristics of individuals with oculocutaneous albinism in Botswana - Thanuja Panicker; Gopinath Madheswaran (African Vision and Eye Health)
Background: Understanding the characteristics of oculocutaneous albinism (OCA) in African populations is crucial for developing appropriate support strategies.